ENGLISH FILMONYM: THE PROBLEM OF ITS TRANSLATION IN THE RUSSIAN FILM INDUSTRY - Pankratova Svetlana A (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The paper deals with the leading trends in the translation of English filmonyms of the last two decades. The topic is new due to the growth of international competition in the film industry, which requires the observance of language norms and authors‟ rights. More than 500 of filmonyms became the object under study, including television, video and animation film titles in English and American English of any genre or volume. These filmonyms are studied with the aim of evaluating the cultural and pragmatic variation between the source filmonym and its translation into the Russian language. The material of the study allows to draw conclusions regarding the perfection of the translation techniques and methods of the home film industry. The main recommendations state the need to observe the balance between source and receiving cultures. The paper implements the method of the synchronous typological comparison, which enables to correlate peculiarities, similarities and differences between filmonyms‟ translations. The results of the study demonstrate ten trends in modern filmonyms‟ translation: dramatisation, jargonizm, infernality, discursiveness, de-personification, explanation, misogyny, negativism, minimal word play and forenization. The paper recommends to to pay attention to the cultural clearness of the language, to offer women-friendly translations, to avoid jargon and to raise educated film-goers by elevating their minds.